The Dynamics of iOS-Based e-Attendance Implementation: A Study on User Experience at Atma Jaya Sub-District Office, North Bengkulu - Fanro, Fanro; Rohati, Nely; Indah , Yuni; Angelia, Loara; Melasari, Okta (JPW (Jurnal Politik Walisongo), 2024)
The digital transformation in government administration has driven the adoption of e-Government, including the iOS-based digital attendance system implemented by the North Bengkulu Regency Government under Regent Circular No: 800.1.9/0285/BKPSDM of 2024. This study analyses user experience with the iOS-based e-attendance application at the Arma Jaya Sub-District Office using a qualitative, exploratory approach through Focus Group Discussions (FGD) involving 18 employees, along with interviews with academics and policymakers. The analysis focuses on efficiency, satisfaction, error rates, and ease of learning. Findings indicate that the application improves attendance recording efficiency, saves time and operational costs, and facilitates employee discipline monitoring. However, network instability often results in recording errors, and some employees find the system lacks advanced features. While this implementation enhances government accountability, improvements in technology infrastructure and employee training are needed to maximize its benefits. In conclusion, although the iOS-based e-attendance system enhances transparency and efficiency, technical barriers highlight the necessity for system upgrades and better infrastructure support to ensure its long-term effectiveness